Evaluation of University Professors. Trends and Critical Issues - Suárez-Monzón, Noemí (2021)
The main objective of this study was to determine trends in the evaluation of university professors by performing a systematic review of 32 research studies between the years 2008 and 2019. A thematic content analysis was used and five trends were identified: 1) macro-policies contextualized into micro-policies, 2) promotional evaluations transitioned to formative and developmental evaluations, 3) using student criteria as a participatory approach, 4) moving from one-dimensional to multidimensional approaches, and 5) switching from an administrative routine process to a strategic process for professors and institutions. Based on the results, critical issues are discussed, including their contributions to the decision making process of policy evaluation. It is concluded that additional studies are needed on policy contextualization processes, evaluation mechanisms, and methodological validation by taking into account regional specificity.